O matriarchacie, bogini-matce i Babie Jadze, czyli najkrótsza historia ludzkości. Na marginesie książki Zygmunta Krzaka - Ziółkowski, Adam (Poznańskie Studia Teologiczne, 2008)
The paper examines a new attempt to resuscitate the matriarchy theory by Zygmunt Krzak. The author endeavours to outline what he considers the main line of development of the human society: the birth of matriarchy in the late Palaeolithic, its neolithic apogee, the rise of patriarchy at the turn from the Chalcolitic to the early Bronze, the relics of matriarchy in the subsequent epochs and the “new era” patriarchy of the last two millennia. The matriarchy hypothesis of Bachofen, Morgan and Engels is treated as a historical fact, decisively corroborated - he adds - by Gimbutas. Like her, he finds the corroborating material in artefacts depicting nude females or female genitals, and in the “evidence” on the so-called Mother-cult, the alleged neolithic worship of a supreme female principle of life and fertility, said to be reflected in goddesses of pagan pantheons and female figures of legend and folklore. One obsolete phantasy drives another, with total disregard of both the state o f our knowledge and the rules of the scholarly argument. Eg. the author does not bother about the legitimacy of reconstructing the features of the postulated neolithic Magna Mater on the basis of the epiphany of Isis in Apuleius the Platonist’s Golden Ass, written six thounsand years after the putative heyday of the pretended archetype of that new Roman deity in the guise of an old Egyptian goddess, one of the main vehicles of syncretic tendencies of the age. Neither does he explain why the overtly erotic images of women, made by men for men, should be treated as evidence for the cult of a supreme fertility goddess, nay, for matriarchy. No wonder that, judging by quotations, his main allies are - apart from Gimbutas - Jung, Fromm and their likes, and the occultists.